Challenges in Diagnosing Parkinson’s Disease vs. Multiple System Atrophy: A Case Report Highlighting MRI as a Key Diagnostic Tool - Tamang, Ongden Yonjen; Maharjan, Santosh; Upadhyaya, Rudra Prasad; Shrestha, Ashish; Shrestha, Gaurab; Chaudhary, Rajiv (Nepalese Journal of Radiology, 2025)
We report a case that outlines the diagnostic challenge faced in differentiating between Parkinson's disease (PD) and multiple system atrophy (MSA) in a 58-year-old man with a history of PD. Despite treatment, the patient exhibited limited response and presented with symptoms suggestive of atypical Parkinsonism, prompting a brain MRI. The MRI revealed characteristic features of MSA, showing putaminal atrophy and altered signal intensity. Differential diagnosis between MSA and PD is crucial, with specific MRI findings serving as key differentiators. Early recognition and differentiation are vital for appropriate management.